Interaction between gold nanoparticles and blood proteins to define disease states. (29th March 2019) - Peitinho, David J.; de Almeida, Miguel P.; Pereira, Eulália; Krippahl, Ludwig; Franco, Ricardo
Abstract : Introduction: Gold Nanoparticles (AuNPs) have been used for several drug delivery applications with promising results, although a detailed model for interaction between AuNPs and biomolecules present in the bloodstream is still lacking [1, 2 ]. Furthermore, some diseases alter the serum protein content profile, influencing the composition of adsorbed proteins at the AuNP surface, the so-called protein corona, indicating a possibility for future diagnostic tools [3 ]. In this work, we study the interaction between blood proteins, such as Albumin (a globular protein with 66 kDa) and Fibrinogen (Fib), a cylindrically-shaped protein with 340 kDa), with AuNPs, in order to improve our understanding of this interaction on a complex protein mixture such as Human Serum. Data from individual proteins can hopefully be used to model AuNP-plasma proteins interaction, as the basis for future studies and applications of AuNPs in the diagnosis of important diseases and in vivo treatment. Materials and methods: Spherical AuNPs with a diameter of ca. 15 nm were chemically synthesized, functionalized with an alkanethiol (11-MUA) to increase their colloidal stability, and further conjugated by simple incubation with Bovine Serum Albumin (BSA) or bovine Fib, used as homologs of their human counterparts. The protein corona was analyzed by Agarose Gel Electrophoresis (AGE), SDS-PAGE, Dynamic Light Scattering (DLS) and Nanoparticle Tracking Analysis (NTA). Zeta-potential values were estimated by Ferguson Plot Analysis of the AGE runs or were determined by Electrophoretic Light Scattering (ELS). Computational methods were applied to the analysis of electrophoretic mobility as observed in video sampling of the AGE runs. Results: Size and concentration of the synthesized AuNPs was determined by UV-vis spectroscopy. rom a Langmuir Isotherm fitting of the observed bioconjugation curves, binding constants were obtained for AuNP-MUA conjugation with BSA (1.5 × 10 −2 ± 0.1), or Fib (34.3 × 10 −2 ± 1.2); and for AuNP-CALNN conjugation with Fib (51.2 × 10 −2 ± 4.7). AuNP-CALNN conjugation with BSA lead to band smearing on AGE, not allowing an evaluation of the binding process. Overnight competitive incubation of a protein mixture with AuNP-MUA, favoured Fib adsorption over BSA. Discussion and conclusions: Electrostatic protein conjugates show a robust structure in AGE runs, with generally low band dispersion, especially for AuNP-MUA conjugates. Video analysis revealed protein corona stabilization and a constant band migration velocity. Binding affinity constants and competitive behaviour confirmed a higher affinity for Fib conjugation over BSA to the functionalized AuNPs. This higher binding affinity for Fib can be explained by its higher surface contact area and a possible cooperativity mechanism, deserving further analysis.